Respuesta :
the first, third, and fourth options are correct, i just took the edginuity test.
Answers
- 2(x2 + 6x + 9) = 3 + 18
- 2(x2 + 6x) = –3
- 2(x2 + 6x) = 3
- x + 3 =
- 2(x2 + 6x + 9) = –3 + 9
- (x + 3)2 =
The steps that she could use to solve the quadratic equation is determined as 2(x² + 6x + 9) = 18 + 3.
Solution to the quadratic equation
The solution to the quadratic equation is determined as follows;
2x² + 12x - 3 = 0
2x² + 12x = 3
divide through by 2
x² + 6x = ³/₂
take half of coefficient of x, square it and add it both sides of the equation
(x + 3)² = ³/₂ + 3²
x² + 6x + 9 = 9 + ³/₂
2(x² + 6x + 9) = 18 + 3
Thus, the steps that she could use to solve the quadratic equation is determined as 2(x² + 6x + 9) = 18 + 3.
Learn more about quadratic equation here: https://brainly.com/question/1214333